EFEKTIFITAS PEMBINAAN AKHLAK TERHADAP PENDIDIKAN AGAMA ISLAM SISWA KELAS VIII MTS AL-WASHLIYAH GEDUNG JOHOR MEDAN TAHUN PELAJARAN 2019/2020 - Pane, Rahmat Fajar (Fakultas Agama Islam, 2020)
This study uses an approach, pedagogical and psychological, with the type of research is field research with qualitative descriptive analysis. The source of the data consists of primary data, namely the principal, students, moral education teachers and Islamic religion. While secondary data is data collected in the form of important documents in MTs Al-Washliyah Johor Johor Building related to research. Data collected through observation, interviews and documentation, then processed through three stages, namely data reduction, data display and data verification and fluffiness. The results showed that the moral development of students in Al-Washliyah MTs, Johor Medan Building can be done with learning strategies of theory and practice as well as coaching through extracurricular activities in the form of habituation, learning and exemplary arranged in daily programs (zuhur prayer and kultum) mingguang program (salat) Friday) the monthly program (recitation) as well as the knowledge program (Islamic boarding school and Islamic commemoration day) of the program showed an increase in the morals of students including honesty, discipline and responsibility. The supporting factors are curriculum, school principals, teachers, parents and students, while the inhibiting factors are the lack of parental supervision, the lack of teachers' example, there are no religious facilities in the school environment. The solution is that parents need to increase the supervision of students when at home, parents and teachers need cooperation in moral development, there needs to be a meeting between the school principal and the teacher council every month to find out the level of teacher guidance for students.